Taqwîm Mahârah Al-Qirâah biwasîlati Qanât Youtube - Charis Anthomi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study is to describe the evaluation of Arabic reading skills by using YouTube as an evaluation medium and to see the phenomena that arise when Youtube is used as an evaluation medium in Arabic reading skills. In this study, researchers used descriptive and analytic methods, because a lot of data were obtained from students who were learning in class by observation and interviews. The results showed that the steps in evaluating reading skills included 3 stages, the first stage was the preparation or video making, then the upload stage, and the last stage was the assessment itself. while the implications that arise when using youtube as an evaluation medium are the increased enthusiasm and motivation of students when reading Arabic, especially when they know they will publish it on youtube, students are more enthusiastic and serious in showing their speaking skills. with the use of youtube as an evaluation medium, the phenomenon of increasing student scores, almost all students get good grades, besides the videos they make can also be used as interesting, fun, and easy learning media.